Improving the Economic Level of Mandar Silk Artisans (Lipa'sa'be) with a Community Development Approach in Limboro District, Polewali Mandar Regency, West Sulawesi Province - Siradjuddin; Umaleu, Urbanus (Jurnal Ilmiah Neraca : Ekonomi Bisnis, Manajemen, Akuntansi, 2025)
This study aims to determine the influence of working capital level, number of workers, working hours on the production value of mandar silk fabric (lipa' sa'be mandar). The research uses a mix method which begins with data mining in a qualitative way using a questionnaire approach, interviews and direct observation/observation in the field. Data collection was carried out by means of focus group discussion to mandar silk weaving sarong artisans using community development and purposive sampling as the main method of determining informants. The population in the study is all home industry entrepreneurs as many as 3,793. A sample of 95 home industries was drawn using the Slovin Formula. The analysis technique used is multiple regression analysis of panel data with eviews 9.0 equipment. The results of the study show that working capital and working hours have a positive and significant effect on the production value of the home production of the Man silk weaving industry.